Innovativeness, Risk-Taking, Proactiveness, and Firm Performance with Learning Organizations as Mediating Variables. - Kadarusman Kadarusman; Siti Rosyafah (Jurnal Manajemen, Strategi Bisnis dan Kewirausahaan, 2022)
ABSTRAK